AB0028 The Abnormal CD4+T Lymphocyte Subset Distribution Shown by Naïve Rheumatoid Arthritis Patients Can be Modulated by Methotrexate Treatment. (9th June 2015) - Bohόrquez, C.; Ruiz, L.; Garcia, C.; Gόmez-La Hoz, A.; Turriόn, A.; Moruno, H.; Pérez, A.; Sánchez, A.I.; Cuende, E.; Movasat, A.; Albarrán, F.; Leόn, M.J.; et al.
Abstract : Background: Mechanisms regulating the chronic autoimmune response in rheumatoid arthritis (RA) are not well understood. However, activated T CD4+ play a pivotal role initiating and perpetuating the chronic inflammation characteristic for the disease. Objectives: Evaluate the number and distribution of circulating CD4+ T lymphocytes and their CD4+ naïve T cells (TN ), central memory (TCM ), non-terminated effector memory (TNTEM ) and terminated effector memory (TTEM ) T cells subsets in a population of recently diagnosed DMARD naive RA patients before and along the first 6 months of methotrexate (MTX) treatment. Methods: The number of circulating CD4+ T lymphocytes, and of their TN, TM, TCM and TEM subsets in fifty untreated patients with RA before MTX treatment and at 3 and 6 months of treatment were assayed using a multiparametric flow cytometry. We also studied twenty-four age- and sex-matched healthy subjects as controls. Results: RA naïve patients show a significant (p<0.05) expansion of the circulating CD4+ TNTEM subset. MTX non responder naïve RA patients show from basal conditions a significative expansion of CD4+ TNTEM lymphocytes and develop significant expansion of CD4+ TCM, and CD4+ TEM lymphocyte subsets along MTX treatment. Conclusions: Recently diagnosed DMARD naive RA patients show involvement of the circulating CD4+ T lymphocytes activation/differentiation stage subsets. MTX treatment show immunomodulatory effects on CD4+ T lymphocyte compartment with different behavior in responder and non-responder patients. Disclosure of Interest: None declared